The role of secure instant messaging applications in medical education: Evaluating student satisfaction in a case-based learning program using Siilo - Shahar, Tali; Tadmor, Offer; Dior, Uri; Porat, Shay; Safrai, Myriam; Ezra, Yosef; Kabiri, Doron (Frontiers in Medicine, 2023)
Background Instant messaging applications for mobile phones have recently grown in popularity among medical personnel, including both physicians and medical students. During the COVID-19 pandemic, medical education was largely transferred to virtual platforms, making such applications an increasingly important tool for medical education. “Siilo” is a secure instant messaging application that was designed for medical professionals, and offers several advantages over other instant messaging services that are vital for its use in medical settings, including information security, data encryption, and a built-in blurring tool to maintain patient privacy. In addition, Siilo allows for the creation of individual folders for each case, enabling users to conduct separate discussions about multiple patients simultaneously. Objective To evaluate student satisfaction in a case-based learning program using Siilo as a medical education tool in improving student learning outcomes and motivation. Methods A case-based learning program was conducted with 24 fifth-year medical students using Siilo to evaluate its effectiveness as a medical education tool. The program was evaluated through the use of pre- and post-program questionnaires and focus group discussions to assess student satisfaction. Results The majority of students (83.3%) were highly satisfied with the Siilo platform and felt that it enhanced their learning experience, and a majority of students (79.1%) reported that the program was highly effective. Students reported that the platform was easy to use and provided a clear and organized way to follow discussions about cases. The focus group discussions further revealed that students appreciated the real-time communication and felt that the use of Siilo helped to improve the quality of communication and collaboration during the learning process. The use of Siilo as a medical education tool was found to contribute to positive relationships between doctors and students and improve student motivation for learning and outcomes. Conclusion These findings suggest that Siilo can be a valuable resource for medical education, particularly due to its secure and convenient features, which are well-suited for use in medical settings. The use of Siilo in a case-based learning program was found to be effective in improving student satisfaction and learning outcomes and contributed to positive relationships between doctors and students. These results highlight the potential for utilizing mobile instant messaging apps as a tool for enhancing clinical teaching in medical education.